Mathew McConnell: Self, Theft and Inspiration - Brown, Glen R. (My University, 2014)
In a moment of wry candour the royal academician Henry Fuseli is said to have remarked that fellow Romantic William Blake was "damned good to steal from". This terse assertion was not likely a confession of guilt. After all, academic training in the late-Georgian era consisted of close copying of the ancients and Old Masters and taste was epitomised in academic circles by the judicious borrowing of figures, compositions and even stylistic traits from paragons of art. Only later in the 19th century, with the advent of modernism and its philosophy of the avant-garde, would an obsession with originality burgeon in the art of the western world and cast Fuseli's utterance in an unflattering light.
Keywords: History in Art; Arts--Exhibitions; Mathew McConnell; Artistic theft; Artistic inspiration